Characteristics and Thirty‐day Outcomes of Emergency Department Patients With Elevated Creatine Kinase. (June 2014) - Grunau, Brian E.; Pourvali, Reza; Wiens, Matthew O.; Levin, Adeera; Li, Jennifer; Grafstein, Eric; Joo, Dan; Scheuermeyer, Frank Xavier; O'Neil, Brian J.
Abstract Objectives Rhabdomyolysis, as defined by an elevation in creatine kinase (CK), may lead to hemodialysis and death in emergency department (ED) patients, but the patient characteristics, associated conditions, and 30‐day outcomes of patients with CK values over 1, 000 U/L have not been described. Methods All consecutive ED patients with serum CK values over 1, 000 U/L between January 1, 2006, and December 31, 2008, were retrospectively identified from two urban hospitals. Patient characteristics, ED treatment, and ED discharge diagnoses were determined by medical record review. Provincial databases were linked to identify patients who died or were treated with hemodialysis within 30 days. The primary outcome was the combined occurrence of death or need for hemodialysis within 30 days. Secondary outcomes included the incidence of acute kidney injury (AKI) and the proportion of patients with initial estimated glomerular filtration rates (eGFR) > 60 mL/min/1.73 m2 who died or required hemodialysis. Results Four‐hundred patients were identified, the median age was 50 years (interquartile range [IQR] = 35 to 69 years), and 77% were male, with 35% of patients discharged home from the ED. The most common ED discharge diagnoses were related to recreational drug use, infections, and traumatic or musculoskeletal complaints. Within 30 days, 32 (8.0%, 95% confidence interval [CI] = 5.3% to 11%) experienced primary outcomes, with 18 (4.5%, 95% CI = 2.55% to 6.5%) requiring hemodialysis and 21 deaths (5.3%, 95% CI = 3.1% to 7.4%). AKI occurred in 151 patients (38%, 95% CI = 33% to 43%). Of the 257 patients (64%) with initial eGFRs > 60 mL/min/1.73 m2, none required hemodialysis. Conclusions In ED patients with initial CK > 1, 000 U/L, the incidence of death or hemodialysis was 8% within 30 days. Patients with initial eGFRs > 60 mL/min/1.73 m2 appear to be at a low risk of these outcomes from rhabdomyolysis.